Prenatal exposure to perfluoroalkyl substances modulates neonatal serum phospholipids, increasing risk of type 1 diabetes. (October 2020) - McGlinchey, Aidan; Sinioja, Tim; Lamichhane, Santosh; Sen, Partho; Bodin, Johanna; Siljander, Heli; Dickens, Alex M.; Geng, Dawei; Carlsson, Cecilia; Duberg, Daniel; Ilonen, Jorma; Virtanen, Suvi M.; et al.
Highlights: Over last decade, increasing incidence of type 1 diabetes has stabilized in Finland. Stabilization of disease incidence coincides with tighter regulation of PFAS. High prenatal PFAS exposure associates with decreased postnatal serum phospholipids. High prenatal PFAS exposure associates with appearance of islet autoantibodies. Prenatal PFAS exposure contributes to increased postnatal risk of type 1 diabetes. Abstract: In the last decade, increasing incidence of type 1 diabetes (T1D) stabilized in Finland, a phenomenon that coincides with tighter regulation of perfluoroalkyl substances (PFAS). Here, we quantified PFAS to examine their effects, during pregnancy, on lipid and immune-related markers of T1D risk in children. In a mother-infant cohort (264 dyads), high PFAS exposure during pregnancy associated with decreased cord serum phospholipids and progression to T1D-associated islet autoantibodies in the offspring. This PFAS-lipid association appears exacerbated by increased human leukocyte antigen-conferred risk of T1D in infants. Exposure to a single PFAS compound or a mixture of organic pollutants in non-obese diabetic mice resulted in a lipid profile characterized by a similar decrease in phospholipids, a marked increase of lithocholic acid, and accelerated insulitis. Our findings suggest that PFAS exposure during pregnancy contributes to risk and pathogenesis of T1D in offspring.